Calculations of visible radiation in electrodeless HID lamps. (June 2016) - Hamady, M; Lister, GG; Zissis, G
This paper compares the measured photometric properties and power balance of a conventional electroded metal halide lamp containing mercury and thallium iodide with those obtained from a theoretical model for discharges sustained by a microwave electromagnetic field. In the calculations, the discharge is assumed to be in the TM010 mode, sustained by a microwave field of frequency 2.45 GHz. The numerical model used to obtain the power balance in the discharge is based on a solution to the Elenbaas–Heller equation for the gas temperature, and a simple 'skin depth' model to describe the penetration of the maintenance electric field in the discharge. A ray tracing method is employed to simulate the radiation transport, to compute the emitted radiation flux, luminous flux, luminous efficacy and the correlated colour temperature. The calculations of the total radiation flux from the discharge as a function of electric power is consistent with previously published calculations, showing that the fraction of electric power converted to radiation increases as electric power increases, provided all other lamp parameters are constant. However, our results indicate that this does not necessarily correspond to an increase in the fraction of electrical power converted to visible radiation.